Experimental studies on cyclic performance of column base weak axis aligned asymmetric friction connection. (September 2015) - Borzouie, J.; MacRae, G.A.; Chase, J.G.; Rodgers, G.W.; Clifton, G.C.
Abstract: Applied cyclic imposed displacement tests are conducted on a column base weak axis aligned asymmetric friction connection (i) in-plane, about the strong axis, (ii) out-of-plane, about the weak axis, and (iii) in a bi-axial clover leaf pattern. Testing is conducted with and without applied axial force and drift ratios ranged from 0.2% to 4%. The base connection tolerated high levels of drift without significant damage. However, some flange compressive yielding occurred when the column was simultaneously subjected to axial force and drifts with significant components in both the strong and weak axis directions. Prying occurred due to loading about the weak axis, but not about the strong axis. Simple models estimated the force–displacement hysteresis loop envelope behaviour. This base connection shows promise for actual construction due to its relatively little damage at large drifts and its low cost. Highlights: New base connection that asymmetric friction connections were used at the base of the steel column parallel to the web (WAFC) is described. The experimental tests on this base connection showed that WAFC can tolerate high levels of drift without significant strength degradation. A simple procedure proposed to estimate the moment resistance is verified. A new torsional demand on a column is described.